2002
DOI: 10.1088/0954-3899/28/7/373
|View full text |Cite
|
Sign up to set email alerts
|

Kaon phase space density in heavy-ion collisions

Abstract: Abstract. The first measurement of kaon phase space densities are presented as a function of m T , √ s nn and the number of participants. The kaon phase space density increases with the number of participants from e + e − to P b+P b collisions. However the ratio of the kaon and pion phase space densities at low P T is independent of number of participants for √ s nn = 17GeV.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…At √ s NN = 17.3 GeV, it was found that strong longitudinal flow could significantly reduce the space-averaged phase-space density of pions [40]. Also at this energy the inverse slope of the phase-space density was found to increase with particle mass in a manner suggestive of transverse flow [41]. Using the fact that the deuteron has energy E d = E n + E p and momentum P = 2p, Eq.…”
Section: B Average Phase-space Densitymentioning
confidence: 98%
“…At √ s NN = 17.3 GeV, it was found that strong longitudinal flow could significantly reduce the space-averaged phase-space density of pions [40]. Also at this energy the inverse slope of the phase-space density was found to increase with particle mass in a manner suggestive of transverse flow [41]. Using the fact that the deuteron has energy E d = E n + E p and momentum P = 2p, Eq.…”
Section: B Average Phase-space Densitymentioning
confidence: 98%
“…Kaons, compared to pions, are expected to be less contaminated by resonance decays [18,20]. In addition the kaon phase space density is much smaller than the pion density [21]. As a consequence, higher multiparticle correlation effects (that may be important for pions at RHIC energies [22]) are possibly under much better control for kaons.…”
Section: Spacetime Evolution and Kaon Interferometrymentioning
confidence: 99%
“…In particular, the kaon density is much lower than the pion density [10]. Hence, multiparticle correlations that might play a role for the pions are of minor importance for the kaons.…”
mentioning
confidence: 98%
“…The correlations of kaons provide a severe test of the pion data and have several advantages [6]. In particular, the kaon density is much lower than the pion density [10]. Hence, multiparticle correlations that might play a role for the pions are of minor importance for the kaons.…”
mentioning
confidence: 99%